Chip‐based electrochromatography coupled to ESI‐MS detection. Issue 10 (15th March 2016) - Dietze, Claudia; Hackl, Claudia; Gerhardt, Renata; Seim, Stephan; Belder, Detlev
Abstract : In this study, we present the coupling of chip‐based electrochromatography to MS using a glass chip with a monolithically integrated nanoelectrospray emitter. As separation column, an acrylate‐based porous polymer monolith is implemented into the glass chip by photopolymerization. For the establishment and development of this method, we used a test mixture detectable with both fluorescence and ESI‐MS. After successful evaluation of the approach with the test solutes, it was applied exemplarily for drug analysis such as high‐speed separations of benzodiazepines in pharmaceuticals.